Performance Analysis of Recycled Asphalt Material Foundation Layer and Top Foundation Layer Reviewed from Primary Displacement - Diyanti; Fani Yayuk Supomo; Sri Indah Setiyaningsih (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the unconfined compressive strength of recycled materials based on variations in cement content of 1%, 3%, and 5%, as well as the percentage of emulsified asphalt. This study is urgently needed because the massive development of road infrastructure drives an increase in the need for road materials. Utilization of recycled waste from existing asphalt layers and foundation layers is an alternative sustainable and environmentally friendly material. Reusing this material is more efficient if the road damage has not reached the structural stage. Testing in the study was conducted experimentally at the Road Materials Center Laboratory, Bandung, using materials from existing asphalt layers and foundations. Testing includes physical analysis of the material, compaction to determine the optimum water content and maximum dry density, and unconfined compressive strength. The results showed that the unconfined compressive strength with cement content of 1%, 3%, and 5% were 0.70 MPa, 1.70 MPa, and 2.09 MPa, respectively, with primary displacement values ​​of 20 mm, 25.8 mm, and 24.7 mm. Meanwhile, the residual strength value decreased with increasing cement content, namely 76.3%, 66.3%, and 64.3%.